Improving the efficiency of the coal grinding process in ball drum mills at thermal power plants - Kamarova, Saule; Abildinova, Saule; Terziev, Angel; Baydusenov, Galym (Eastern-European Journal of Enterprise Technologies, 2022)
Ensuring the reliable operation of the dust fuel preparation system at thermal power plants (TPP) is a topical issue since it determines the energy strategy of any country that fires coals for thermal energy production. This unit is one of the most energy-intensive units in TPP. Those systems are outdated, poorly automated and high energy-intensive. Furthermore, they must ensure efficient and safe operation of the facility while being environmentally friendly. The current work focuses on the process of grinding coals in ball drum mills for further pulverized combustion. An experimental study was performed in order to determine the main factors (rotational speed of the drum mill, the degree of loading with the grinding balls, and the velocity of the supplied air) that affect the efficiency of the fuel preparation system. The obtained experimental data and performed mathematical modeling resulted in regression equations describing the energy performance of the mill. Three regression equations for mill productivity, power consumed, and specific surface area of the final product were obtained and validated. The study reveals that the lowest specific energy consumption is achieved when the relative rotational speed of the mill is between 0.81 and 0.87; the weighted average diameter of the balls ranges from 33.5 up to 34.5 mm; the load factor of the grinding media ranges from 0.325 up to 0.335, the supplied air velocity is between 0.2 and 0.3 m/s. The proposed methodology allows adjustment of the operating parameters of the grinding process to achieve the lowest energy consumption. The power consumption for the preparation can be reduced up to 5 % for the selected operation mode of the grinding facility.